Kesadaran Anti-Bullying Siswa Normal Terhadap Siswa Berkebutuhan Khusus Kelas Xl di SMKN 7 Padang - Pramuja. F, Melati; Nurhastuti, Nurhastuti (Inovan Publisher, 2024)
One of the phenomena that has taken a lot of attention in the world of education is bullying that occurs in schools so that the phenomenon that is done by peers in Indonesia continues to increase. School bullying is a worldwide problem that can have lifelong negative consequences for students. One of them is bullying by normal students towards students with special needs in public schools. This study used a quantitative descriptive method which aims to determine the state of anti-bullying of normal students against students with special needs in class Xl at SMK N 7 Padang. Respondents in this study were forty normal students in class Xl. The results of this study indicate that efforts to prevent and see the bullying of normal students are quite good for students with special needs. So it can be concluded that the anti-bullying awareness of normal students is quite good for students with special needs in class Xl at SMK N 7 Padang.